Proceedings of the 2018 Library Assessment Conference: Building Effective, Sustainable, Practical Assessment: December 5–7, 201 2019
DOI: 10.29242/lac.2018.29
|View full text |Cite
|
Sign up to set email alerts
|

Qualifying for Services: Investigating the Unmet Needs of Qualitative Researchers

Abstract: This study investigates the needs of qualitative researchers and the ways in which libraries may address some of those needs. Using qualitative interview methods, we conducted 10 semi-structured interviews with individuals from two stakeholder groups: researchers (faculty and doctoral students) and librarians. Among the variety of needs that emerged, ranging from methods training to identifying sources of funding, we discuss two implications for library practice in detail: (1) the need for depth in library res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…As social sciences librarians who work frequently with researchers using a wide range of methodological approaches, we have found that work around data literacy and research data services programming often seems based on the assumption that data is inherently quantitative. This observation is supported by recent research by Cain et al (2019), Pearce et al (2019), andSwygart-Hobaugh (2016) on the difficulty of locating support for qualitative research in academic libraries.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…As social sciences librarians who work frequently with researchers using a wide range of methodological approaches, we have found that work around data literacy and research data services programming often seems based on the assumption that data is inherently quantitative. This observation is supported by recent research by Cain et al (2019), Pearce et al (2019), andSwygart-Hobaugh (2016) on the difficulty of locating support for qualitative research in academic libraries.…”
Section: Introductionsupporting
confidence: 58%
“…The few existing needs analyses indicate that qualitative researchers would benefit from a research data infrastructure that supports their work throughout the research cycle, from preparing IRB applications and research design to analyzing data and writing research reports in ways that meets the expectations of readers who may not work in the same research paradigm (Downing et al, 2019). Even when research data services are available for qualitative work, individual researchers are often unaware of such services and see the library primarily as a site of collections access rather than for active methodological learning (Pearce et al, 2019).…”
Section: Academic Library Support For Qualitative Researchmentioning
confidence: 99%